Islamic Economic Analysis Reviewing Top Up Transparency Practices and Effective Flat Installment Systems in Banking - Astuti, Rahma Yudi; Wijanarko, Royhan Muhammad Iqbal (prodima@fe.uika-bogor.ac.id, 2024)
The background of the writing is because there are customers who are stuck with the facilities provided by the bank, namely top up (addition of loans) and Effective Flat Installments which it is not known what exactly the two facilities are. by the bank first, the customer will receive a new schedule and a new loan limit. Of course, the bank will choose the criteria for customers who will be given top up facilities, namely the history of installment payments is relatively smooth, this is precisely the root of the problem that many customers experience who do not understand about top ups and an effective flat installment system. Lack of transparency about what will be done by the customer in the future imposed by the bank to the customer so that the customer bears a lot of losses caused by the top up and the effective flat installment system. This research is a qualitative research with an evaluative-normative approach. The purpose of this study was to determine the extent to which the transparency applied by the banking sector for top-up loans, as well as the application of the flat installment system was effectively implemented. application of the principle of transparency in implementing Bank Indonesia regulations and how the practice of transparency is viewed from the Islamic economy.